Expansion of a Language Project at the UCR Pacific Campus: Correct Actions and Challenges - López Montero, Rosberly (2020)
This paper analyzes the impact of the outreach Language project ED-2884 at the Pacific Regional Center of Universidad de Costa Rica in terms of its extension to communities surrounding the university campus. It describes the most relevant correct actions and challenges faced during this process. The paper reveals an increase in the project’s impact in the region, letting a bigger population access language learning. At the same time, it details the challenges the project must face to keep a quality offer of courses available in such communities.